2017
DOI: 10.1007/s11934-017-0744-1
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Imaging Modalities Used in the Diagnosis and Management of Scrotal Trauma

Abstract: Genitourinary tract injuries account for 3 to 10% of trauma patients, and scrotal trauma is particularly prevalent in males 10 to 30 years of age. Prompt diagnosis and timely surgical intervention are essential to prevent future complications of infertility, delayed orchiectomy, infection, and testicular atrophy. While clinical examination provides valuable information, it may be inconclusive due to soft tissue swelling and difficult to perform due to testicular pain with palpation. Conversely, testicular rupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…Ultrasound is often the first diagnostic tool beyond a physical exam that is used to evaluate blunt scrotal trauma given it is a non-invasive, expeditious, and essentially ubiquitous technology. Ultrasonographic findings which may help with accurate clinical diagnosis have been adapted from Wang and Fenton and are outlined in Table 1 1 , 2 . In one of the larger published series, Buckley and McAninch retrospectively reviewed 65 patients with blunt scrotal trauma over a 25 year period and found that a heterogeneous parenchymal echo pattern with loss of testicular contour is highly sensitive (100%) and specific (93.5%) for testicular rupture or testicular torsion 3 …”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is often the first diagnostic tool beyond a physical exam that is used to evaluate blunt scrotal trauma given it is a non-invasive, expeditious, and essentially ubiquitous technology. Ultrasonographic findings which may help with accurate clinical diagnosis have been adapted from Wang and Fenton and are outlined in Table 1 1 , 2 . In one of the larger published series, Buckley and McAninch retrospectively reviewed 65 patients with blunt scrotal trauma over a 25 year period and found that a heterogeneous parenchymal echo pattern with loss of testicular contour is highly sensitive (100%) and specific (93.5%) for testicular rupture or testicular torsion 3 …”
Section: Discussionmentioning
confidence: 99%
“…e di erential diagnosis of scrotal injuries is myriad and includes epididymitis, orchitis, incarcerated inguinal hernia, testicular infarction, testicular fracture or rupture, testicular torsion, appendicular torsion, dislocated testes, hydrocele, or hematocele [6]. Clinical examination may be di cultpatients are o en reluctant to be examined due to pain and so tissue swelling can make the testes di cult to palpate [3].…”
Section: Discussionmentioning
confidence: 99%
“…e main goal of US is to assess the vascular perfusion and integrity of the testes and distinguish testicular rupture from other injuries. Using modern ultrasound equipment, a sensitivity, and speci city of 95-100% for diagnosing testicular rupture is now possible [6,9]. e normal tunica albuginea in US appears as a thin echogenic line surrounding the testicular parenchyma and is challenging to appreciate especially in the presence of scrotal contusion [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations